La pulsión comunitaria en la obra de Diamela Eltit - Barrientos, Mónica (Latin America Research Commons, 2019)
Diamela Elite's community idea is a political position that conjugates art and life that proposes a direct dialogue with Jean-Luc Nancy's concept of literary communism. It is a practice of articulating diverse plural voices from a common space that limits with the opening towards the other, forming an act of communication that involves "the communist interruption of the class domain, of social stratifications and of power, it is proposed to write in its expanded character," that is, different types of graphic inscriptions, somatographic and performative in general.